The role of visceral and subcutaneous adipose tissue measurements and their ratio by magnetic resonance imaging in subjects with prediabetes, diabetes and healthy controls from a general population without cardiovascular disease - Storz, Corinna; Heber, Sophia D; Rospleszcz, Susanne; Machann, Jürgen; Sellner, Sabine; Nikolaou, Konstantin; Lorbeer, Roberto; Gatidis, Sergios; Elser, Stefanie; Peters, Annette; Schlett, Christopher L.; Bamberg, Fabian (British journal of radiology, 2018)
Objective: To study the relationship of area- and volumetric-based visceral and subcutaneous adipose tissue (VAT and SAT) by MRI and their ratio in subjects with impaired glucose metabolism from the general population. Methods: Subjects from a population-based cohort with established prediabetes, diabetes and healthy controls without prior cardiovascular diseases underwent 3 T MRI. VAT and SAT were assessed as total volume and area on a single slice, and their ratio (VAT/SAT) was calculated. Clinical covariates and cardiovascular risk factors, such as hypertension and glycemic state were assessed in standardized fashion. Univariate and adjusted analyses were conducted. Results: Among 384 subjects (age: 56.2 ± 9.2 years, 58.1% male) with complete MRI data available, volumetric and single-slice VAT, SAT and VAT/SAT ratio were strongly correlated (all >r = 0.89). Similarly, VAT/SATvolume ratio was strongly correlated with VATvolume but not with SAT (r = 0.72 and r = −0.21, respectively). Significant higher levels of VAT, SAT and VAT/SAT ratio were found in subjects with impaired glucose metabolism (all p ≤ 0.01). After adjustment for potential cardiovascular confounders, VATvolume and VAT/SATvolume ratio remained significantly higher in subjects with impaired glucose metabolism (VATvolume = 6.9 ± 2.5 l and 3.4 ± 2.3 l; VAT/SATvolume ratio = 0.82 ± 0.34 l and 0.49 ± 0.29 l in patients with diabetes and controls, respectively, all p < 0.02), whereas the association for SATvolume attenuated. Additionally, there was a decreasing effect of glycemic status on VAT/SATvolume ratio with increasing body mass index and waist circumference (p < 0.05). Conclusions: VATvolume and VAT/SATvolume ratio are associated with impaired glucose metabolism, independent of cardiovascular risk factors or MRI-based quantification technique, with a decreasing effect of VAT/SATvolume ratio in obese subjects. Advances in knowledge: Quantification of VATvolume and VAT/SATvolume ratio by MRI represents a reproducable biomarker associated with cardiometabolic risk factors in subjects with impaired glucose metabolism, while the association of VAT/SATvolume ratio with glycemic state is attenuated in obese subjects.
Gesehen am 20.04.2020